Eksistensi Ilmu Falak dari Masa Nabi Syits hingga Masa Nabi Idris - Mutiara Tembang Langit; Ahmad Izzuddin (Astroislamica: Journal of Islamic Astronomy, 2025)
This paper attempts to examine the historical development of astronomy, focusing on the lineage from Prophet Seth to Prophet Idris. Prophet Idris, as a descendant of Prophet Adam, plays a central role in the development of astronomical science. He is considered one of the pioneers in this field, with significant contributions in formulating and recording various astronomical knowledge. This paper aims to uncover the origins, evolution, and significant contributions of the prophets in the development of astronomy since the time of Prophet Adam. This paper relies on qualitative data collected through library research, using descriptive historical analysis of various sources, including religious texts and related literature. With this research framework, it was found that astronomy has been an integral part of human civilization since the time of Prophet Adam. This research also highlights the development of astronomy. The lineage of Prophet Adam serves as a framework for understanding how scientific knowledge, including astronomy, has developed in the context of agriculture, calculation, and prediction.